Regional constraints to biological nitrogen fixation in post‐fire forest communities. Issue 3 (1st March 2013) - Yelenik, Stephanie; Perakis, Steven; Hibbs, David
Abstract : Biological nitrogen fixation (BNF) is a key ecological process that can restore nitrogen (N) lost in wildfire and shape the pace and pattern of post‐fire forest recovery. To date, there is limited information on how climate and soil fertility interact to influence different pathways of BNF in early forest succession. We studied asymbiotic (forest floor and soil) and symbiotic (the shrub Ceanothus integerrimus ) BNF rates across six sites in the Klamath National Forest, California, USA. We used combined gradient and experimental phosphorus (P) fertilization studies to explore cross‐site variation in BNF rates and then related these rates to abiotic and biotic variables. We estimate that our measured BNF rates 22 years after wildfire (6.1–12.1 kg N·ha −1 ·yr −1 ) are unlikely to fully replace wildfire N losses. We found that asymbiotic BNF is P limited, although this is not the case for symbiotic BNF in Ceanothus . In contrast, Ceanothus BNF is largely driven by competition from other vegetation: in high‐productivity sites with high potential evapotranspiration (Et), shrub biomass is suppressed as tree biomass increases. Because shrub biomass governed cross‐site variation in Ceanothus BNF, this competitive interaction led to lower BNF in sites with high productivity and Et. Overall, these results suggest that the effects of nutrients play a larger role in driving asymbiotic than symbiotic fixation across our post‐fire sites. However, because symbiotic BNF is 8–90× greater than asymbiotic BNF, it is interspecific plant competition that governs overall BNF inputs in these forests.